POLLUTER PAYS PRINCIPLE DALAM KETENTUAN PERUNDANGAN PENGELOLAAN AIR LIMBAH DOMESTIK DI KECAMATAN CIRACAS JAKARTA TIMUR - Wisnu Anindito Wiraatmaja; Sapto Hermawan; Asianto Nugroho (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
People's daily activities for cooking, bathing, washing, latrines, produce household domestic wastewater which has the potential to cause water pollution, both well water and river water. This is exacerbated by the lack of public awareness of the environment and low public understanding of the Polluter Pays Principle. This research was conducted to identify the understanding of the people of Ciracas District, the provisions and implementation, the alignment of the provisions of the legislation related to the management of domestic wastewater, as well as the obstacles faced in its implementation. It is concluded that the public's understanding of the Polluter Pays Principle is still low. The construction of a domestic wastewater management installation in the Kampung Rambutan Reservoir can be a real step in an effort to increase public awareness in managing domestic wastewater. The alignment of the provisions of laws and regulations regarding the application of the Polluter Pays Principle in domestic household wastewater management still needs to be improved. The obstacle in its implementation is the lack of formal and informal education for the community about domestic wastewater management. The role of the government which is felt to be less than optimal is also an obstacle in growing public awareness in managing domestic wastewater. In addition, plans for the development of a domestic wastewater management system are generally also constrained by the low participation and resistance of the community.